S49 Identifying patient suitability for lung volume reduction – estimation of gas trapping from spirometry. (December 2018) - Elbehairy, AF; Whittaker, H; Quint, JK; Buttery, S; Jordan, S; Polkey, MI
Abstract : Background: Lung volume reduction (LVR) procedures can improve quality of life, exercise capacity and survival in carefully selected people with chronic obstructive pulmonary disease (COPD). The optimum strategy to identify possible candidates has not yet been defined. The presence of hyperinflation is a key suitability criterion but access to body plethysmography is limited. Aim: To evaluate a recently reported model to estimate residual volume (RV) (measured by body plethysmography, RVpl) using a prediction equation based on spirometry values (RVest). Methods: Validation data-set: retrospective analysis of 846 COPD patients with spirometry and plethysmography. Estimated RV was calculated as follows: [RVest%=3.58(FVC%)−164(FEV1 /FVC)−81(SQRT-FVC%)−0.83(age) −10.7(gender) +732, where male=1, female=0]. An FEV1 <50% and an RV of ≥175%predicted were used to define potential suitability for LVR. Results: RVpl and RVest were 210±59 and 183%±32%predicted (mean ±SD), respectively. The prevalence of RV ≥175%predicted was 72% and 64% in RVpl and RVest, respectively (p=0.001). Mean difference between RVpl and RVest was 27.8%±42.3% and 95% limits of agreement was −55% and 111%. Agreement between the two measurements was better at lower RV values (figure 1). RV <175% cut-off had the highest sensitivity (0.79) and specificity (0.83) compared with higher cut-offs; when this was combined with FEV1 >50%predicted, sensitivity and specificity were 0.94 and 0.94 (and positive and negative predictive values were 0.72 and 0.91). Conclusion: Estimation of RV from standard spirometry can identify patients with COPD who could to benefit from LVR where further detailed investigation may be appropriate.